Aplicación de un sistema contable para el comercial “Mi Ferretería”, de la ciudad de Loja, periodo septiembre-noviembre del 2014 - Ochoa Merino, María del Cisne (2015)
Considering the importance of the knowledge acquired in university classrooms and as a prerequisite for obtaining the Bachelor of Accounting and Auditing, Auditor CPA requirement, the preparation of this paper entitled "Implementation of an accounting system for the commercial" MI is justified HARDWARE "CITY OF LOJA, between September-November 2014". With the application of accounting in the company under study, it was possible to meet the proposed objectives at the beginning of the period; Thus, the lifting of economic information was made through the development of an initial inventory values for assets, liabilities and equity held by the company at 01 September this year. Plan and Accounting Manual for the type of activity performed by the business was structured. The books and aids were designed; where economic information generated was recorded from September to November. Sorted and processed the information structure was achieved and presenting the financial statements such as: the Income Statement, Statement of Financial Position and Cash Flow Status, where the current situation is reflected hardware. For these reasons; It was concluded that it is vital that every company adopted an accounting system for the control and registration of operations, which will assess it in their actions and their ability to generate revenue and profit, factors that will be known through Presentation of Financial Statements; therefore, it is recommended to its owner, adopting the model presented consistently so you can have reliable information regarding the progress of your company